The Corporate Social Responsibility of companies and its effects on competitive advantage : a comparative analysis of Botswana and South Africa - Van Heerden, C.M. (Corlia) (University of Pretoria, 2017)
Mini Dissertation (LLM)--University of Pretoria, 2016.